Aggregate shocks and the Brazilian housing market dynamics - Marcelo Eduardo Alves da Silva; Cássio da Nóbrega Besarria; Diogo Baerlocher (EconomiA, 2019)
In this paper we seek to understand the recent dynamics of the Brazilian housing market, which experienced a significant growth in recent years. In particular, we assess the effects of aggregate productivity and monetary policy shocks on housing market variables. Moreover, we also investigate the effects of shocks to housing prices that are orthogonal to business cycle movements. We use a SVAR approach with sign restriction backed by a Dynamic Stochastic General Equilibrium (DSGE) model estimated for Brazil. The empirical results show that the housing market responds positively to aggregate productivity shocks, while a contractionary monetary policy shock depress housing output, demand and prices. Additionally, we find monetary policy as an important source of variation in housing prices and financing, while productivity shocks explain a substantial share of housing production movements. We also show that the behavior of housing prices is mostly driven by shocks to housing prices that are orthogonal to business cycles movements.
Keywords: E32; E52; R21; R31; 330; Housing markets; Business cycle; Monetary policy; DSGE; SVAR models; Sign restrictions